LEKSEM BERKONSEP âRUSAKâ DALAM BAHASA JAWA DIALEK SURAKARTA (ANALISIS SEMANTIK) - , DEWI FATHONA RAHMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study is about \"Lexeme concept 'damage' in Javanese Surakarta dialect (Semantic Analysis)\". In this case, the boundaries of 'damage' is' not intact'. This study describes about relation of meaning and the component meaning lexemes in Javanese Surakarta dialect in 'damage' concept. The data is lexeme with âdamageâ concept in Javanese Surakarta dialect which derived from field interviews and dictionary search. Data was analyzed by using meaning relation and meaning component theory. The results are presented in formal and informal forms. The results show that there are seven categories of the meaning field which is category berlubang, lepas, robek, patah, pecah, roboh dan hancur. The conclusion is a lexeme must have a different meaning component with another lexemes. Keywords : lexeme , damage , meaning field , dialect Surakarta